UANG DALAM PRESPEKTIF EKONOMI ISLAM (DEPRESIASI NILAI RUPIAH) - Nurlaili, Nurlaili (IKONOMIKA, 2016)
Abstract-In Islamic economics, which is recognized only function of money as a medium of exchange and unity count (unit of account). Money itself does not provide usability , but the money that provides utility functions. Money becomes useful when exchanged for the real thing or if it is used to purchase services. Therefore, money can not be commodities  that can be traded.This study uses qualitative descriptive method in order to determine the economic outlook of Islam on the function of money.The concept of money in Islamic economics is different from the conventional concept of money in the economy. Islamic economics, the concept of money is very clear and unequivocal that money is money is not capital. Average money in an economic perspective konvensionl interpreted inter change ability / commute, ie money as money and as capital.According to the money capitalist system not only serves as a medium of exchange but money also could be traded. Instead, the Islamic view of money that the money is used only as a medium of exchange (medium of exchange) not as a commodity. In Islam, anything that serves as money, then its function as a medium of exchange. Furthermore, an important phenomenon in the characteristics of money is that it is not necessary for consumption, it is not necessary for himself, but needed to buy other goods that human needs can be met.